Waris dalam Tinjauan Keadilan dan Kemanfaatan Q.S. al-Nisā’ Ayat 11-12 Perspektif Amina Wadud - Sama’un, Sama’un; Bahrudin, Ahmad (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
In inheritance law, the Qur’an typically stipulates a 2:1 distribution, where men receive two parts and women one. This division is often justified by the idea that men are responsible for earning a living, with women not typically involved in financial support. However, feminist exegete Amina Wadud argues that this distribution is not based on justice. She emphasizes that the primary consideration in inheritance should be the benefits the heirs will receive, rather than gender. This study aims to analyze inheritance distribution in Qs. al-Nisā’ verses 11-12 from Amina Wadud's feminist perspective, specifically her critique of the 2:1 ratio. The study is a qualitative library research study titled "Inheritance in the Review of Justice and Benefit Perspective Amina Wadud." The primary source is Wadud's book Women in the Qur'an and the Qur'an According to Women, with secondary sources drawn from related articles and journals. The findings indicate that while the Qur'an generally assigns men a larger share, inheritance is not always distributed in a 2:1 ratio. The division varies depending on factors such as family relationships, with sometimes equal shares (1:1) or a different distribution (1:2), prioritizing justice and the benefits of the heirs.